Self-Efficacy, Lifestyle, and Quality of Life in Older Adults: A Literature Review (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2021)
In adulthood, the development and maintenance of healthy lifestyle habits during the aging process is a promising strategy to reduce disease-related complications, prevent premature death, and ensure healthy aging. However, neglecting health during the aging process leads to complex changes in physical, psychological, and social health, which gradually deteriorate overall well-being and reduce perceived quality of life.The aim of this review was to analyze the benefits of self-efficacy and lifestyle on various physical, psycho-emotional, social health variables, and quality of life in older adults. A systematic literature review was conducted for the period 2011 to 2020. Out of a total of 288 eligible articles according to the inclusion criteria, 40 studies were selected for final analysis.The results indicate that self-efficacy is a reinforcement tool for self-care to achieve healthy habit goals. To promote healthy aging and a better perception of quality of life, a healthy lifestyle is recommended, with key strategies including accumulated physical activity, structured exercise, and a balanced diet in older adults. Self-efficacy and lifestyle programs have been shown to improve different areas of behavior in older adults, suggesting that future research should consider multidisciplinary interventions targeting various aspects of comprehensive health behavior in this population.